2016
DOI: 10.1016/j.reprotox.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Maternal phthalate exposure during early pregnancy and at delivery in relation to gestational age and size at birth: A preliminary analysis

Abstract: Epidemiologic studies of in utero phthalate exposure and birth outcomes have had conflicting findings. The objective of this study was to characterize maternal phthalate exposure across pregnancy, examine associations between maternal phthalate levels and infant size and gestational age at birth, and investigate relationships between concurrent bisphenol A (BPA) and phthalate exposure and birth outcomes. Women in the Michigan Mother-Infant Pairs cohort provided urine and blood samples during their first trimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 56 publications
(89 reference statements)
1
62
0
Order By: Relevance
“…Our most conservative paternal model included gestational age as a covariate. Several recent studies have also found suggestive sex-specific patterns in birth weight in relation to some prenatal phthalate metabolites and similarly report increased birth weight among boys but not girls (Watkins et al 2016; Casas et al 2016; Sathyanarayana et al 2016). …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our most conservative paternal model included gestational age as a covariate. Several recent studies have also found suggestive sex-specific patterns in birth weight in relation to some prenatal phthalate metabolites and similarly report increased birth weight among boys but not girls (Watkins et al 2016; Casas et al 2016; Sathyanarayana et al 2016). …”
Section: Discussionmentioning
confidence: 82%
“…Substantial experimental evidence in animals shows that phthalates are developmental and reproductive toxicants (Lyche et al 2009; Lovekamp-Swan and Davis 2003; Gray et al 2000; Marsman 1995; Tanaka 2002; Lamb et al 1987; Gray et al 2006). While there has been legitimate emphasis on studying the effects of prenatal phthalate exposure in humans, these studies have largely produced inconsistent findings due in part to considerable heterogeneity in design, study population and methods (Marie et al 2015; Louis et al 2008; Smarr et al 2015; Watkins et al 2016; Casas et al 2016; Sathyanarayana et al 2016). Given that phthalates may exert effects on both gametes and embryos, studies assessing exposure before conception as well as during pregnancy are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of ln-transformed EDCs was examined across categories of sociodemographic and perinatal characteristics using simple linear regression for continuous variables and ANOVA with post-hoc Tukey HSD for categorical variables to identify potential confounders. To adjust for urine dilution in linear regression analyses, urinary SG was included as a covariate in models using continuous urinary EDC variables, as we have done previously [31]. In fully adjusted models, the child's sex, maternal pre-pregnancy body mass index (BMI) and maternal age were included as potential confounders based on a priori expectations informed by previous studies and current literature.…”
Section: Methodsmentioning
confidence: 99%
“…Spot urine samples were collected into polypropylene urine collection containers, aliquoted into glass vials, and frozen at ¡80 C until analysis. Urinary BPA (56 out of the cohort of 116) and nine phthalate metabolites (109 out of the cohort of 116), comprising monoethyl phthalate (MEP), mono-n-butyl phthalate (MnBP), monoisobutyl phthalate (MiBP), monobenzyl phthalate (MBzP), mono-3-carboxypropyl phthalate (MCPP), mono-2ethylhexyl phthalate (MEHP), mono-2-ethyl-5-hydroxyhexyl phthalate (MEHHP), mono-2-ethyl-5-oxohexyl phthalate (MEOHP), and mono-2-ethyl-5-carboxypentyl phthalate (MECPP), were measured at NSF International in two batches (Ann Arbor, MI) using isotope dilution-liquid chromatographytandem mass spectrometry (ID-LC-MS/MS) as previously described [31]. Summary measures for parent compounds di-(2ethylhexyl) phthalate (SDEHP) and dibutyl phthalate (SDBP) for each sample were calculated by dividing their respective individual metabolite concentrations by their molar mass and summing them.…”
Section: Phthalate Metabolite and Bpa Measurementmentioning
confidence: 99%
“…Though we are unable to probe the relationship between the human embryonic yolk and these parturition outcomes, the use of models such as the zebrafish may help to elucidate this relationship. Epidemiology studies have associated numerous environmental toxicants with reduced birth weight or size, including bisphenol A [81], phthalates [82], perfluorinated compounds [83, 84], and fine particulate matter [85]. However, the mechanisms underlying this relationship remain unknown.…”
Section: Uncovering the Role Of Embryonic Nutrition In The Developmenmentioning
confidence: 99%